2005
DOI: 10.1111/j.1365-2885.2005.00668.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of glycosylated undenatured type‐II collagen (UC‐II) in therapy of arthritic dogs§

Abstract: DeParle L. A., Gupta R. C., Canerdy T. D., Goad J. T., D'Altilio M., Bagchi M., Bagchi D. Efficacy and safety of glycosylated undenatured type-II collagen (UC-II) in therapy of arthritic dogs. J. vet. Pharmacol. Therap.28, 385-390. In large breed dogs, arthritis is very common because of obesity, injury, aging, immune disorder, or genetic predispositions. This study was therefore undertaken to evaluate clinical efficacy and safety of undenatured type-II collagen (UC-II) in obese-arthritic dogs. Fifteen dogs in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(81 citation statements)
references
References 16 publications
4
65
0
Order By: Relevance
“…Native type II collagen has been found to be effective in reducing arthritic pain in animal models [10][11][12] as well as in improving clinical outcomes in patients with rheumatoid arthritis [7][8][9]. However, few studies have evaluated the efficacy of native type II collagen in osteoarthritis [13,14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Native type II collagen has been found to be effective in reducing arthritic pain in animal models [10][11][12] as well as in improving clinical outcomes in patients with rheumatoid arthritis [7][8][9]. However, few studies have evaluated the efficacy of native type II collagen in osteoarthritis [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have evaluated the efficacy of native type II collagen in osteoarthritis. In animal trials, it has been found effective in reducing arthritic pain [10][11][12]. In human trials, native type II collagen has been found effective in increasing functional status and reducing pain [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The placebo group contained only two dogs because IACUC advised us to keep to a minimum number of dogs due to the fact that arthritic dogs suffer from inflammation and pain for a period of five months. Moreover, findings of our previous studies revealed that dogs receiving placebo showed no improvement in arthritis pain [19][20][21][22][23]. Nine dogs in Group-II received Crominex 3+ (500µg of trivalent chromium, 7.5 mg Phyllanthus emblica extract, and 7.5 mg purified Shilajit) twice daily (one capsule before morning meal and one capsule before evening meal) for a period of five months.…”
Section: Experimental Designmentioning
confidence: 99%
“…Pain after limb manipulation, on a scale of 0-4, was evaluated as: 0, no pain; 1, mild pain; 2, moderate pain; 3, severe pain; and 4, severe and constant pain. Pain after physical exertion, on a disease modifying agents and physical therapy with acupuncture have been used [19][20][21][22][23][31][32][33][34][35]. In the recent past, to manage OA in canine patients, most veterinarians have commonly used cyclooxygenase (COX) inhibiting non-steroidal anti-inflammatory drugs (NSAIDS), such as deracoxib, etodolac, carprofen, firocoxib, ketoprofen, meloxicam, rofecoxib, tepoxalin and others [36,37].…”
Section: Pain Measurementmentioning
confidence: 99%
See 1 more Smart Citation